Milk Substitutes Selected Aspects - Ziarno, Małgorzata (IntechOpen, 2021)
This book presents certain aspects of the consumer, nutritional, and technological approach to plant-based milk substitutes. It also provides a useful overview of cow's milk substitutes produced from raw materials along with their composition and quality, shelf life, nutritional value, human health significance, and consumer acceptance. Nutrition issues and consumer acceptance of plant-based foods are extremely important, especially for vegans or individuals with allergy and intolerance issues. These issues are also important for the agriculture industry in developing countries, as they also apply to feed farm animals.